'[Expletive], that was confusing, wasn't it?' Defence lawyers' and intermediaries' assessment of the language used to question a child witness. (October 2018) - Hanna, Kirsten; Henderson, Emily
While language specialists and legal professionals have voiced concerns about the language used to question child witnesses in the Aotearoa/NZ courts, it is unclear whether both groups share a common understanding of what those language problems are. This study compares five Aotearoa/NZ defence lawyers' and two England/Wales intermediaries' perceptions of the developmental (in)appropriateness of the language used to question an 11-year-old witness, based on their assessment of the witness' anonymised trial transcript. The comparison showed that both groups agreed on the categories of language features that might confuse children, however, intermediaries identified many more instances of problematic language within those categories than lawyers. Training on developmentally appropriate language and pre-trial preparation of questions would certainly help lawyers improve the comprehensibility of their questions. However, the implementation of a full intermediary scheme, such as that in England/Wales, probably offers the best prospects for a sustained sea change in questioning practices.